Life Interpretation and the Sense of Illness within the Human Condition
XXI, 287 p.
Keywords: In medicine the understanding and interpretation of the complex reality of illness currently refers either to an organismic approach that focuses on the physical or to a 'holistic' approach that takes into account the patient's human sociocultural involvement. Yet as the papers of this collection show, the suffering human person refers ultimately to his/her existential sphere. Hence, praxis is supplemented by still other perspectives for valuation and interpretation: ethical, spiritual, and religious. Can medicine ignore these considerations or push them to the side as being subjective and arbitrary? Phenomenology/philosophy-of-life recognizes all of the above approaches to be essential facets of the Human Condition (Tymieniecka). This approach holds that all the facets of the Human Condition have equal objectivity and legitimacy. It completes the accepted medical outlook and points the way toward a new `medical humanism'.